Binding activity of duffy binding protein (PkDBPaII) of Plasmodium Knowlesi clinical isolates from Peninsular Malaysia and Malaysian Borneo / Lim Khai Lone - Lim, Khai Lone (2018)
The zoonotic Plasmodium knowlesi is a major cause of human malaria in Malaysia. This parasite uses the Duffy binding protein (PkDBPαII) to interact with the Duffy antigen receptor for chemokines (DARC) receptor on human and macaque erythrocytes to initiate invasion. Previous studies on P. knowlesi have reported distinct Peninsular Malaysia and Malaysian Borneo PkDBPαII haplotypes. Notably, patients with knowlesi malaria in Malaysian Borneo often present with hyperparasitemia and more severe disease compared to patients in Peninsular Malaysia. Therefore, it is our interest to determine the implication of the genetic variation of PkDBPαII from Peninsular Malaysia and Malaysian Borneo on binding activity and affinity to erythrocytes. In this study, the differential binding activity of these haplotypes with human and macaque (Macaca fascicularis) erythrocytes was investigated through Erythrocyte-binding assays (rosettes formation assays) and their binding affinities (KD) were determined using Isothermal Titration Calorimetry (ITC) analysis. The PkDBPαII of Peninsular Malaysia and Malaysian Borneo were expressed on the surface of COS-7 cells and tested with human and monkey erythrocytes, with and without anti-Fy6 (anti-Duffy) monoclonal antibody treatment. Binding activity level was determined by counting the number of rosettes formed between the transfected COS-7 cells and the erythrocytes. Anti-Fy6 treatment was shown to completely block the binding of human erythrocytes with the transfected COS7 cells, thus verifying the specific binding of human DARC with PkDBPαII. Interestingly, the PkDBPαII of Peninsular Malaysia displayed a higher binding activity with human erythrocytes when compared to the Malaysian Borneo PkDBPαII haplotype (mean number of rosettes formed = 156.89 ± 6.62 and 46.00 ± 3.57, respectively; P < 0.0001). iv However, no difference in binding activity level was seen in the binding assay using Macaca fascicularis erythrocytes. This finding was further supported by ITC, whereby the PkDBPαII of Peninsular Malaysia and Malaysian Borneo were expressed as recombinant proteins using Escherichia coli expression system. The expressed PkDBPαII recombinant proteins were affinity purified and refolded back to native state prior to the biomolecular interaction analysis with human erythrocytes. The result showed that the binding affinity of PkDBPαII-Peninsular Malaysia (KD value = 7.75 µM) was higher than PkDBPαII in Malaysian Borneo (KD value = 74.1 µM). This study is the first report of phenotypic difference between PkDBPαII haplotypes. The biological implication of this finding is yet to be determined. Therefore, further studies need to be carried out to determine whether this differential binding level is associated with disease severity of knowlesi malaria in humans.